Hayama Industries - A production system study - Galarosa, Iris (College of Engineering, 1992)
Hayama Industrial Corporation is a Filipino-owned Corporation. It has business address at 1100 North Edsa, Quezon City, Philippines. It has a plant situated at the company's business address covering an approximate area of 4,295 square meters. Among the products it manufactures are (1) bottle conveyors, (2) crate conveyors, (3) pressure vessels, (4) sanitary tanks and (5) pressure and sanitary piping works. Aside from these products, the company also does rehabilitation and refurbishing activities and turnkey projects. Currently, the company is faced with major problems such as: (1) Material Requirements are hard to fill. (2) Work scheduling is difficult. (3) Responsibility for manufacturing defects cannot be pinpointed. (4) The plant is idle between jobs. (5) There is confusion on what materials should be kept as inventory. (8) Lack of manpower usually exists for some bottleneck operations. In the study and analysis of the proponents on the problems on Hayama's Production system, they have come up with the following recommendations: (1) Import specialized parts for a job order instead of manufacturing it in the plant. (2) Proceed with the next scheduled job during lead times. When there is no job waiting on queue, do maintenance programs. In addition to maintenance programs, conduct group dynamics activities for worker to worker relations improvement. (3) Clarify lead times with suppliers and state it explicitly to client company. (4) Per order have one worker currently employed do the quality inspection. Assignment of who should be the quality inspector should be done on rotation. Inspection will be done after every operation. (5) Hire 2 Industrial Engineering students one summer vacation period to conduct a study on what materials are to be kept as inventory. Keep a small inventory of all these materials. (6) Conduct monthly tool checks. (7) Penalize workers responsible with 50%of current price of missing tool, if there is any. (8) Train workers on all tasks (9) Advertise products in newspaper on weekends, limiting ads to 6 lines per issue.